Safety and efficacy of pulse-induced contour cardiac output monitoring in elderly patients with coronary artery disease and severe heart failure at coronary care units - Li-ping, Qi; Hong-wei, Liu; Chang-ming, Hong; Yong-yi, Bai; Ang, Li (Frontiers in Cardiovascular Medicine, 2022)
Abstract： Background: The optimal treatment for elderly patients with severe heart failure depends on the accurate assessment of their hemodynamic status. Due to its less invasive nature, the safety and efficacy of invasive pulse-induced contour cardiac output (PiCCO)-based hemodynamic monitoring remains uncertain. Methods: This was a prospective observational study. Between January 2016 and July 2020, 190 elderly patients with severe heart failure were consecutively enrolled. The PiCCO group (89 patients) and noninvasive hemodynamic monitoring group (101 patients) were observed. Hospital stays results were evaluated. Results: No significant difference in clinical data(P>0.05) or the incidence of one-month mortality(16.0% vs. 35.0%, P=0.141) were observed between groups. The coronary care unit (CCU) stay was shorter in the PiCCO group than in the noninvasive group(40.0% vs. 43.0%, P=0.049). Indicators such as low Extravascular Lung Water Index (EVLWI), high Body Mass Index (BMI), low Pulmonary Artery Pressure (PAP), and high Left Ventricular Ejection Time (LVET), were associated with favorable clinical results. Conclusion: Early invasive PiCCO monitoring is safe in critically ill elderly patients with severe heart failure. The hospital stay was reduced using PiCCO monitoring. These encouraging PiCCO results favor its use in elderly patients with severe heart failure at CCUs.